2017
DOI: 10.1192/bjp.bp.116.183475
|View full text |Cite|
|
Sign up to set email alerts
|

Interaction between the FTO gene, body mass index and depression: meta-analysis of 13701 individuals

Abstract: BackgroundDepression and obesity are highly prevalent, and major impacts on public health frequently co-occur. Recently, we reported that having depression moderates the effect of the FTO gene, suggesting its implication in the association between depression and obesity.AimsTo confirm these findings by investigating the FTO polymorphism rs9939609 in new cohorts, and subsequently in a meta-analysis.MethodThe sample consists of 6902 individuals with depression and 6799 controls from three replication cohorts and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
28
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 54 publications
(35 citation statements)
references
References 44 publications
5
28
0
2
Order By: Relevance
“…According to a recent systematic review of genome-wide association and candidate gene studies pleiotropic genes, such as the FTO gene, may underlie (Amare et al 2017), but findings are however, inconsistent (Walter et al 2015). Also interactions between genotype, such as the FTO gene, depression and BMI have been reported (Clarke et al 2015;Rivera et al 2017). On the other hand, both depression (Osborne et al 2016;Chen et al 2017;Edvinsson et al 2017) and BMI (Dick et al 2014;Ligthart et al 2016) Behavioral mechanisms may also be involved, including sleep problems and pain that may be aggravated in higher BMI pregnancies and that may induce more depressed feelings.…”
Section: Discussionmentioning
confidence: 99%
“…According to a recent systematic review of genome-wide association and candidate gene studies pleiotropic genes, such as the FTO gene, may underlie (Amare et al 2017), but findings are however, inconsistent (Walter et al 2015). Also interactions between genotype, such as the FTO gene, depression and BMI have been reported (Clarke et al 2015;Rivera et al 2017). On the other hand, both depression (Osborne et al 2016;Chen et al 2017;Edvinsson et al 2017) and BMI (Dick et al 2014;Ligthart et al 2016) Behavioral mechanisms may also be involved, including sleep problems and pain that may be aggravated in higher BMI pregnancies and that may induce more depressed feelings.…”
Section: Discussionmentioning
confidence: 99%
“…The homozygous mutation of FTO gene can reduce the brain capacity of healthy elderly people, increase the susceptibility to brain atrophy during aging, and even affect the brain volume of adolescents [117,118]. The genetic polymorphism of FTO is related to attention-deficit/hyperactivity disorder (ADHD), Alzheimer's disease and depression [119][120][121][122][123][124]. Whether it is as demethylase that affects these diseases, is worthy of further study.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, the situation of being diagnosed with depression of the individuals was investigated based on a personal declaration in this study. In one study, it was reported that the BMI of individuals with depression who had risk allele was 2.2% higher and increased the effect of FTO [27]. Therefore, it is considered that it will be useful to evaluate this situation by considering the depression status in the future studies.…”
Section: Discussionmentioning
confidence: 99%